CONCEPTUAL FOUNDATIONS OF KEY PERFORMANCE INDICATOR (KPI) SYSTEMS AND THEIR ROLE IN CONTEMPORARY ORGANIZATIONAL MANAGEMENT (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the conceptual foundations of Key PerformanceIndicator (KPI) systems and their role in contemporary organizational management.Drawing on classical and modern management theories, including the BalancedScorecard framework and performance measurement system literature, the study exploreshow KPIs function as strategic tools for aligning organizational activities with longterm objectives. The research highlights core principles of KPI design, such as strategicalignment, balance, and adherence to SMART criteria, as well as the importance ofvalidity and reliability in measurement systems. Furthermore, the article analyzesgovernance mechanisms, including ownership, monitoring processes, and integrationinto decision-making structures. Particular attention is given to common implementationchallenges, such as misalignment with strategy, data quality issues, and insufficientmanagerial commitment. The study also investigates the impact of digital transformationon KPI systems, emphasizing the role of dashboards, real-time analytics, and emergingtechnologies in enhancing organizational performance. The findings suggest that welldesigned and effectively governed KPI systems significantly improve decision-making,accountability, and strategic execution in modern organizations.
Keywords: Key Performance Indicators (KPIs); Performance Measurement Systems; Balanced Scorecard; Strategic Management; Organizational Performance